Innovations in Soft Computing and Information Technology Proceedings of ICEMIT 2017, Volume 3 - Chattopadhyay, Jayeeta; Singh, Rahul; Bhattacherjee, Vandana; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book presents innovative scientific research works by academics, research scholars and students, presented at the 2017 International Conference on Energy, Materials and Information Technology at Amity University Jharkhand, India. It includes contributions on system solutions based on soft computing techniques, and covers innovative soft computing techniques and tools with advanced applications. A major focus of the book is on presenting interdisciplinary problems and how they can be solved using information technology, together with innovative connections to other disciplines. It also includes papers on cloud computing and WSN-related real-time research. .
Chapter 1. Sinusoids and it's Orthogonality -- Chapter 2. A Case Study of Hindi-English Example Based Machine Translation -- Chapter 3. Comparative Study of Different Machine Learning Models for Breast Cancer Diagnosis -- Chapter 4. A PID Load Frequency Controller Design via Pole Placement and Approximate Frequency Response Matching. etc.
Keywords: Telecommunication; Signal processing; Application software; Communications Engineering, Networks; Signal, Speech and Image Processing .; Computer and Information Systems Applications